FULFILLMENT OF THE NEEDS OF SHIP BERTHING FACILITIES TO ENSURE PASSENGER SAFETY AT THE PIER OF THE CENGKLIK RESERVOIR BOYOLALI DISTRICT CENTRAL JAVA PROVINCE - Sulistiyono, Noor; Sutrisno, Slamet Prasetyo; Sutrisno, Sri Kelana; Aziz, Dadang Abdul; Nugroho, Aji (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
Boyolali Regency is one of the regencies in Central Java Province that has a lake/ reservoir as a water tourism site. Cengklik Reservoir has 37 tour boats that operate around the Cengklik Reservoir. The purpose of this research was to determined the berthing facilities needed at the reservoir and determined the type of pier that used at Cengklik Reservoir. This study was conducted from February to May 2024 by obtaining data on the characteristics of the data, reservoir water elevation data, water level data, and ship passenger productivity data. This study used several methods to solve existing problems, namely analyzing the need for docking facilities, analyzing the type of dock needed, analyzing the type of fender and bolder and analyzing the number of fenders and bolder. Based on the analysis, it was concluded that the smoothness of passenger loading and unloading activities and the safety of passengers when boarding / disembarking the ship were influenced by berthing facilities that meet the requirements that are in accordance with the needs. The need for ship berthing facilities at Cengklik Reservoir is planned to ensure passenger safety by determining the type of mobile type pier with dimensions of 31, 46 meters long and 8, 58 meters wide with planned berthing facilities in the form of fenders with a total of 29 units and a distance of 1, 07 meters, bolder with a total of 14 units with a distance of 2, 33 meters.